Long Noncoding Ribonucleic Acid MSTRG.59589 Promotes Porcine Skeletal Muscle Satellite Cells Differentiation by Enhancing the Function of PALLD - Li, Long; Cheng, Xiaofang; Chen, Ling; Li, Jingxuan; Luo, Wenzhe; Li, Changchun (Frontiers in Genetics, 2019)
Skeletal muscle satellite cells are a class of undifferentiated mononuclear myogenic stem cells distributed between the myofibroblast and membrane basement. Since their development determines the development of skeletal muscles, knowledge of their proliferation, differentiation, and fate is vital for understanding skeletal muscle development. Increasing evidence have shown that long noncoding RNA (lncRNA) plays an important role in regulating the development process of satellite cells. Based on the results of our previous studies, we screened lncRNA MSTRG.59589, which is highly expressed in skeletal muscle tissue. In the present study, knockdown of MSTRG.59589 significantly inhibited satellite cell differentiation at various time points, whereas overexpression of MSTRG.59589 demonstrated opposite effects. An MSTRG.59589 knockdown cell model was constructed for transcriptome sequencing, and RNA-seq analysis screened out a large number of differentially expressed genes. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses of these differentially expressed genes revealed that they are mainly enriched in actin cytoskeleton, muscle contraction, and other pathways related to muscle development. Mechanistic analyses showed that MSTRG.59589 could promote the differentiation process of skeletal muscle satellite cells by positively regulating the expression level of the target gene PALLD. This experiment lays a theoretical foundation for deeper studies on the mechanism of MSTRG.59589 in the differentiation of porcine skeletal muscle satellite cells